Kompetensi Profesional Guru dalam Proses Pembelajaran - Syarifah Widya Ulfa; Ade Suryani Nasution; Ardina Khoirunnisa Hasibuan; Azzahra Natasya; Budiman Budiman; Khairul Azmi; Masriyanti Nasution (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study aims to explore the concept of teacher professionalism in the 21st century, especially in the context of English language learning. This research uses a qualitative method with a phenomenological design, with data collection techniques through interviews, classroom observations, and document analysis. The results show that teacher professionalism covers various aspects, including subject matter mastery and professional attitude. Professional teachers are expected to be able to design and implement effective learning, motivate students, guide and provide counseling, assess students’ learning progress, and manage the classroom well. The research findings show that English teachers in Indonesia need to improve some aspects of their professionalism, such as English teaching skills in the classroom and the development of more innovative materials. Teachers also need further training to improve their ability to teach English in the digital era. Support from the school and collaboration with peers are also very important to improve the quality of English learning in schools. This study concludes that teacher professionalism is an important factor in achieving better education standards. Teachers must continue to learn and develop to improve their competencies and meet the needs of students in the 21st century.